2021
DOI: 10.1055/a-1546-8415
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of timed barium esophagram after per-oral endoscopic myotomy to predict clinical response

Abstract: Background and study aims The aim of this study was to evaluate whether timed barium esophagram within 24 hours post-per-oral endoscopic myotomy (POEM) (TBE-PP) could predict clinical outcomes. Patients and methods This was a single-center retrospective study of prospectively collected data on consecutive patients with ≥ 6-month follow-up who underwent POEM followed by TBE-PP. Esophageal contrast retention 2 minutes after TBE-PP was assessed as Grade 1 (< 10 %), 2 (10 %–49 %), 3 (50 %–89 %) or 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Therefore, findings for which intervention is not necessary should not be regarded as AEs Original article [19,33]. Performing routine esophagram 1 day post-POEM to assess delay in passage of contrast does not predict long-term efficacy of POEM, and thus, is not useful for that purpose either [34,35]. This is the first study comparing AEs after POEM in patients with and without routine esophagram 1 day post-POEM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, findings for which intervention is not necessary should not be regarded as AEs Original article [19,33]. Performing routine esophagram 1 day post-POEM to assess delay in passage of contrast does not predict long-term efficacy of POEM, and thus, is not useful for that purpose either [34,35]. This is the first study comparing AEs after POEM in patients with and without routine esophagram 1 day post-POEM.…”
Section: Discussionmentioning
confidence: 99%
“…POEM appeared to be safe when performed by experienced endoscopists [4,7,8,9,10,11,12]. However, the definition and classification of adverse events (AEs) varies between studies, and therefore, the number of AEs are wide-ranging from 0% to 35.8% [9,10,12,13,14,15,16,17,18]. Initially, all types of mucosal injury and gas-related events such as pneumoperitoneum and pneumomediastinum were reported as AEs.…”
Section: Introductionmentioning
confidence: 99%
“…These findings add to recent literature about follow-up and testing after POEM. An esophagram <24 hours after POEM does not predict clinical response or risk of GERD (11). Furthermore, normal FLIP metrics by EGJ-DI are equivalent to a normal IRP by HRM to predict clinical response (12).…”
Section: Discussionmentioning
confidence: 99%
“…In another paper by DeWitt et al 8 in 2021, which evaluated the use of TBE after POEM, it was reported that contrast emptying rate by esophagogram after POEM has limited utility to predict clinical response or risk of postprocedure gastroesophageal reflux disease.…”
Section: Methods To Assess Poem Failure—timed Barium Esophagogram (Tb...mentioning
confidence: 99%